Cultured Human Thymic-Derived Cells Display Medullary Thymic Epithelial Cell Phenotype and Functionality - Villegas, José A.; Gradolatto, Angeline; Truffault, Frédérique; Roussin, Régine; Berrih-Aknin, Sonia; Le Panse, Rozen; Dragin, Nadine (Frontiers in Immunology, 2018)
Thymic epithelial cells are one of the main components of the thymic microenvironment required for T-cell development. In the present work, we describe an efficient method free of enzymatic and facs-sorted methods to culture human medullary thymic epithelial cells without affecting the cell phenotypic, physiologic and functional features. Human mTECs are obtained by culturing thymic biopsies explants. After 7 days of primo-culture, mTEC keep their ability to express key molecules involved in immune tolerance processes such as autoimmune regulator, tissue specific antigens, chemokines and cytokines. In addition, the cells sensor their cultured environment and consequently adjust their gene expression network. Therefore, we describe and provide a human mTEC model that may be used to test the effect of various molecules on TEC homeostasis and physiology. This method should allow the investigations of the specificities and the knowledge of human mTECs in normal or pathological conditions and therefore discontinue the extrapolations done on the murine models.